Recent status of levamisole resistance in selected goat farms in kota bharu and bachok, kelantan - Nur Alawiyah Mohd Awalluddin (2023)
Anthelmintic resistances is a widespread problem in small ruminant industry. Levamisole was the only anthelmintic that was found to be effective against gastrointestinal nematode in goat farms in Kelantan about 10 years ago. However, the current status of levamisole in Kelantan is still unknown. Hence, this study aims to investigate the latest status of levamisole resistances in selected goat farms located in Kelantan. The study was conducted on goat farms located in Bachok (n=1) and Kota Bharu (n=1). The goats in these farms were screened for the criteria of Faecal Egg Count Reduction Test (FECRT) and divided into control and treatment groups with approximately similar means of faecal egg count (FEC). Faecal samples that were collected during pre- and post-treatments were subjected to McMaster and faecal culture. The obtained data was recorded and analysed by an automated FECRT spreadsheet. Reduction of posttreatment mean FEC were observed in both farms. Faecal Egg Count Reduction percentage (FECR%) of 88% and 100% were observed in Farm 1 and Farm 2 respectively. Infective stage larvae (L3) identification revealed three genera of gastrointestinal nematode namely Oesophagostomum sp., Trichostrongylus sp. and Haemonchus contortus which predominant the infection. This study shows levamisole resistance has been developed in Farm1. Farm 2 status was observed with low count thus levamisole resistance was not suspected in this farm. Keyword: Anthelmintic resistance, levamisole, FECRT, FECR%, infective stage larvae